2021
DOI: 10.1007/s11207-021-01888-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Suprathermal Electrons in Small-Scale Magnetic Flux Ropes and Their Implications on the Magnetic Connection to the Sun

Abstract: Small-scale magnetic flux ropes (SMFRs) are observed more frequently than larger-scale magnetic flux ropes (e.g., magnetic clouds) in interplanetary space. We selected 235 SMFRs by applying cylindrical linear force-free fitting to 20-year observations of the Wind satellite, which meets the criteria of low beta, low temperature, an enhanced magnetic field, and a rotation feature. By examining the pitch angle distribution of suprathermal electrons for these events, we found that approximately 45.1% of the SMFRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…One may expect different types of reconnection-generated magnetic structures at the boundaries of HS and PS regions due to the topological differences, for example as discussed by Edmondson & Lynch (2017) and Higginson & Lynch (2018), but further numerical modeling of their origin and heliospheric evolution will be needed. This work complements previous statistical studies characterizing magnetic field and plasma properties within coherent intervals or by solar wind type (e.g., Ko et al 2018;Borovsky et al 2019;D'Amicis et al 2019;Borovsky et al 2021), as well as those studies of specific, small-scale structures (Khabarova et al 2021;Gershkovich et al 2022) such as small magnetic flux ropes (e.g., Feng et al 2008;Yu et al 2016;Murphy et al 2020;Choi et al 2021). Importantly, our attempt to relate various in situ properties of the structured variability in slow-to-moderate speed solar wind through an application of the H m -PVI methodology represents a significant extension of previous work where coherent magnetic structures identified "by eye" were shown to be coincident with structure in the proton density and A He observations (e.g., Kepko et al 2016;Di Matteo et al 2019).…”
Section: Summary and Discussionsupporting
confidence: 78%
“…One may expect different types of reconnection-generated magnetic structures at the boundaries of HS and PS regions due to the topological differences, for example as discussed by Edmondson & Lynch (2017) and Higginson & Lynch (2018), but further numerical modeling of their origin and heliospheric evolution will be needed. This work complements previous statistical studies characterizing magnetic field and plasma properties within coherent intervals or by solar wind type (e.g., Ko et al 2018;Borovsky et al 2019;D'Amicis et al 2019;Borovsky et al 2021), as well as those studies of specific, small-scale structures (Khabarova et al 2021;Gershkovich et al 2022) such as small magnetic flux ropes (e.g., Feng et al 2008;Yu et al 2016;Murphy et al 2020;Choi et al 2021). Importantly, our attempt to relate various in situ properties of the structured variability in slow-to-moderate speed solar wind through an application of the H m -PVI methodology represents a significant extension of previous work where coherent magnetic structures identified "by eye" were shown to be coincident with structure in the proton density and A He observations (e.g., Kepko et al 2016;Di Matteo et al 2019).…”
Section: Summary and Discussionsupporting
confidence: 78%
“…In this case, we can imagine that the flux rope axis makes a significant azimuthal angle to the background IMF direction, consistent with the main finding in the present work. On the other hand, Choi et al (2021) have shown that the majority of low-β SMFRs at 1 au (practically the same event group as examined in the present paper) are connected to the Sun at one end (thus open field lines), and there is a very small fraction of SMFRs with closed field lines. Therefore, it needs to be verified whether flux ropes generated by interplanetary HCS reconnection meet this observational constraint for magnetic connectivity to the Sun.…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, it has been suggested (Yurchyshyn 2008;Kay et al 2015;Szabo et al 2020) that significant evolution of solar ejecta (for example, a tendency to align with the HCS) occurs during propagation through interplanetary space, possibly changing their axial orientations (say, at 1 au) from those at generation points near the Sun. However, although many SMFRs are found near the HCS, some are not (Choi et al 2021). Therefore, if most SMFRs were indeed launched near the Sun, a possible propagation effect implies that some other mechanism in interplanetary space, whether close to the HCS or not, must play a significant role in the robust statistical trend of the axial orientations found at 1 au in the present paper.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations